2003
DOI: 10.1016/j.compbiolchem.2003.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic models with maximum entropy production in irreversible charge transfer steps

Abstract: Steady-state bacterial photosynthesis is modelled as cyclic chemical reaction and is examined with respect to overall efficiency, power transfer efficiency, and entropy production. A nonlinear flux-force relationship is assumed. The simplest two-state kinetic model bears complete analogy with the performance of an ideal (zero ohmic resistance of the P-N junction) solar cell. In both cases power transfer to external load is much higher than the 50% allowed by the impedance matching theorem for the linear flux-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 39 publications
0
56
0
Order By: Relevance
“…For example, Kleidon and Fraedrich [2004] have shown that global biotic productivity corresponds to the states of MEP. Juretic and Zupanovic [2003] found that the MEP may govern the photosynthetic processes. Evidence accumulated so far suggests that the MEP theory could explain transport phenomena in the far from equilibrium systems over a wide range of space and time scales [Kleidon and Schymanski, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kleidon and Fraedrich [2004] have shown that global biotic productivity corresponds to the states of MEP. Juretic and Zupanovic [2003] found that the MEP may govern the photosynthetic processes. Evidence accumulated so far suggests that the MEP theory could explain transport phenomena in the far from equilibrium systems over a wide range of space and time scales [Kleidon and Schymanski, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Although the MEP principle is rigorously valid only in a network of linear biochemical reactions they have found that this principle works very well even in the case of a non-linear network of biochemical reactions. Among other applications of the MEP principle we single out ones used to predict rate constants in relevant transitions of bacteriorhodopsin light-cycle and bacterial photosynthesis [40] and an optimal angular position for the ATP-binding transition in the ATPase nanomotor [41]. The successful applications of the MEP principle to these intramolecular transitions (predictions in qualitative agreement or close to experimental values) has encouraged us to test this principle as physical selection principle acting in concert with enzyme biological evolution.…”
Section: Discussionmentioning
confidence: 99%
“…In this section we will present a brief analysis of some photosynthetical reactions within the context of finite-time thermodynamics [2], [5][6][7][8], [10]. In particular, we will use the so-called ecological criterion [10].…”
Section: Comparison Of the Photosynthesis Ecological Functionsmentioning
confidence: 99%
“…De Vos [4], conceived the photosynthesis engine as composed by two parts: a photovoltaic component that absorbs the solar radiation and converts it into work, and a chemical reactor, which uses the work in order to keep a chemical reaction going on in the "reverse direction". A very complete model was proposed by Juretic and Zupanovic [5]. This model is based on a non-equilibrium thermodynamics approach provided by Meszena and Westerhoff [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation